Potential links between brown adipose tissue, circadian dysregulation, and suicide risk - Sarlon, Jan; Partonen, Timo; Lang, Undine E. (Frontiers in Neuroscience, 2023)
Circadian desynchronizations are associated with psychiatric disorders as well as with higher suicidal risk. Brown adipose tissue (BAT) is important in the regulation of body temperature and contributes to the homeostasis of the metabolic, cardiovascular, skeletal muscle or central nervous system. BAT is under neuronal, hormonal and immune control and secrets batokines: i.e., autocrine, paracrine and endocrine active substances. Moreover, BAT is involved in circadian system. Light, ambient temperature as well as exogen substances interact with BAT. Thus, a dysregulation of BAT can indirectly worsen psychiatric conditions and the risk of suicide, as one of previously suggested explanations for the seasonality of suicide rate. Furthermore, overactivation of BAT is associated with lower body weight and lower level of blood lipids. Reduced body mass index (BMI) or decrease in BMI respectively, as well as lower triglyceride concentrations were found to correlate with higher risk of suicide, however the findings are inconclusive. Hyperactivation or dysregulation of BAT in relation to the circadian system as a possible common factor is discussed. Interestingly, substances with proven efficacy in reducing suicidal risk, like clozapine or lithium, interact with BAT. The effects of clozapine on fat tissue are stronger and might differ qualitatively from other antipsychotics; however, the significance remains unclear. We suggest that BAT is involved in the brain/environment homeostasis and deserves attention from a psychiatric point of view. Better understanding of circadian disruptions and its mechanisms can contribute to personalized diagnostic and therapy as well as better assessment of suicide risk.